Association of Irisin Serum Concentration and Muscle Strength in Normal-Weight and Overweight Young Women - Martínez Muñoz, Ilse Yessabel; Camarillo Romero, Eneida del Socorro; Correa Padilla, Trinidad; Santillán Benítez, Jonnathan Guadalupe; Camarillo Romero, María del Socorro; Montenegro Morales, Laura Patricia; Bravo, Gabriel Gerardo Huitrón; Garduño García, José de Jesús (Frontiers in Endocrinology, 2019)
Abstract Background Irisin is a muscle contraction induced miokine, it has been related with exercise type, fitness and physical activity in previous studies however evidence is not consistent. Thus, the aim of this study was to investigate the association between fitness related to health with irisin in young women. Methods Study design prospective cross sectional study. Young, healthy and non smoking women were enrolled.Components of health related fitness, metabolic parameters, serum irisin and body composition were analyzed. Results Sample was conformed by 40 overweight (OW) and N=40 normal weight (NW) subjects. Average age was 18.63 ± 0.63and 18.78 ± 0.73years old respectively. Statistically significant differences were found in physical tests between NW and OW groups; one leg standing test hand grip strenght vertical jump, modified push-up, fitness indexandmaximal oxygen uptake (VO2MÁX). There were no differences in serum irisin concentration between both groups. We found a positive correlation between irisin and hand grip strenght (r =0.374 p< 0.023). In a multivariate analysis adjusted by body fat, a significative association between irisin and hand grip strength was observed in OW group(β =0.380 p< 0.026), and a positive association between irisin and one legstanding testin NW group (β = 0.311 p< 0.044) was shown. Conclusions According to our findings, hand grip strength could be linked with irisin concentration in overweigth young women.